2019
DOI: 10.1155/2019/7589853
|View full text |Cite
|
Sign up to set email alerts
|

Standardized Uptake Value Using Thyroid Quantitative SPECT/CT for the Diagnosis and Evaluation of Graves’ Disease: A Prospective Multicenter Study

Abstract: The clinical applications of the quantitative single photon emission computed tomography (SPECT)/computed tomography (CT) are being expanded to a variety of fields of nuclear medicine. However, clinical application of quantitative SPECT/CT for the evaluation of Graves’ disease (GD) still needs further investigation. Our aim was to investigate the feasibility of standard uptake value (SUV) of the thyroid for the clinical diagnosis and evaluation of GD. In this prospective multicenter study, 116 patients diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 24 publications
2
18
0
Order By: Relevance
“…In this study, the sensitivity, specificity, accuracy, positive predictive rate, and negative predictive rate of 99m TcO 4 -SPECT in the diagnosis of thyroid disease were 95.2%, 90.3%, 91.5%, 94.3%, and 89.6%, respectively. e area under the curve of 99m TcO 4 -SPECT for thyroid disease diagnosis was 0.958, with a 95% confidence interval of 0.834 to 1, which indicated that SPECT imaging can accurately locate the lesion and obtain anatomical information, greatly reducing the misdiagnosis rate of 99m TcO 4 imaging, which was consistent with the results of Dong et al [20].…”
Section: Discussionsupporting
confidence: 88%
“…In this study, the sensitivity, specificity, accuracy, positive predictive rate, and negative predictive rate of 99m TcO 4 -SPECT in the diagnosis of thyroid disease were 95.2%, 90.3%, 91.5%, 94.3%, and 89.6%, respectively. e area under the curve of 99m TcO 4 -SPECT for thyroid disease diagnosis was 0.958, with a 95% confidence interval of 0.834 to 1, which indicated that SPECT imaging can accurately locate the lesion and obtain anatomical information, greatly reducing the misdiagnosis rate of 99m TcO 4 imaging, which was consistent with the results of Dong et al [20].…”
Section: Discussionsupporting
confidence: 88%
“…Kitajima et al 19 reported a case of periosteal sarcoma in a 10-year-old female patient, along with quantitative values obtained with bone SPECT/CT, which were useful to evaluate treatment response to preoperative chemotherapy. Dong et al 20 indicated SUV measurements derived from thyroid SPECT/CT may be useful for the clinical diagnosis and evaluation of Graves' disease. Arvola et al 21 showed that the strong correlation between SUVs and similar SUV ratios of 99m Tc-HDP SPECT/CT and 18 F-NaF PET/CT demonstrate that SPECT is an applicable tool for clinical quantification of bone metabolism in osseous metastases in breast and prostate cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, doctors are unable to analyze changes in the standardized uptake value for imaged tumors if the patient has been examined with different scanners, even in the same nuclear medicine department. Clinical publications reporting SUVmax and SUVmean measured in patients' images should provide SPECT/CT acquisition parameters, but also details regarding the image reconstruction technique [20][21][22][23]. This would allow for an initial comparison of quantification results for pathological changes in images acquired with different SPECT/CT systems.…”
Section: Comparison Of Suvs Acquired For a Single Calibration Sourcementioning
confidence: 99%